Patients’ satisfaction on service quality provision in Champasack provincial hospital - PHOMPHITHAK, Chansy; LUANGSOMBATH, Soulichanh; SYSAVATH, Somphane; HOMESOMBAT, Sisouphanh; PHOTHILADTH, Ammalin (Souphanouvong University Journal Multidisciplinary Research and Development, 2021)
Satisfaction surveys are increasingly being suggested as a means to understand the service expectations and perceptions of patients in hospitals. The objectives of the study was to measure the patients’ satisfaction in service quality provision in Champasack provincial hospital. The survey conducted at Pakse City, provides useful information on the determinants of patient satisfaction across the five dimensions of service quality (SERVQUAL), namely tangible, reliability, responsiveness, assurance and empathy, comprised comprising 23 items for measuring both expected and perceived scores. From the study, patients highly expected services from hospital officials. They needed respected and compromised matter in treatment. They also acquired privacy in treatment and directly diagnosed their health with doctors who specialized in the field. They required staffs to look after and could deal with problems they are received treatment in the hospital. They needed doctors to explain their symptoms and the way how to cure. Also, they indicated that comfort and visual appearance of physical facilities and availability of well-maintained are potential to respond the requirement in service quality.